Size-controlled Pd Nanoparticles Supported onα-Al2O3 as Heterogeneous Catalyst for Selective Hydrogenation of Acetylene - 张火利 杨元一 戴伟 鲁树亮 于海波 吉媛媛 (Chinese journal of chemical engineering, 2014)
Size-controlled Pd nanoparticles （PdNPs） were synthesized in aqueous solution, using sodium car-boxymethyl cellulose as the stabilizer. Size-controlled PdNPs were supported onα-Al2O3 by the incipient wetness impregnation method. The PdNPs onα-Al2O3 support were in a narrow particle size distribution in the range of 1-6 nm. A series of PdNPs/α-Al2O3 catalysts were used for the selective hydrogenation of acetylene in ethylene-rich stream. The results show that PdNPs/α-Al2O3 catalyst with 0.03%（by mass） Pd loading is a very effective and sta-ble catalyst. With promoter Ag added, ethylene selectivity is increased from 41.0%to 63.8%at 100 ＆#176;C. Comparing with conventional Pd-Ag/α-Al2O3 catalyst, PdNPs-Ag/α-Al2O3 catalyst has better catalytic performance in acety-lene hydrogenation and shows good prospects for industrial application.